SYARAT GURU DALAM SERAT WIRID HIDAYAT JATI KARYA RADEN NGABEHI RONGGOWARSITO : (Perspektif Filsafat Jawa) - Permadi, Danur Putut; Wahyudi, M. Agus (LP3M STIT Al Urwatul Wutsqo Jombang, 2022)
A teacher is an important part of the world of education. For this reason, the teacher must have expertise in the teaching field. One of the skills needed by a teacher is about the personality of a teacher who is right. But today there are still teachers who have not been able to make new breakthroughs and prefer to apply traditional learning. This is one of the causes of education in our country problematic. Seeing this is considered necessary to provide an evaluation in the field of education. In Serat Wirid Hidayat Jati is explained that not everyone can become a teacher. This study analyzed the requirement to become a teacher in Serat Wirid Hidayat Jati. By using the literature study method, researchers concluded that a teacher in the Java world was a reflection of a king. He had a big influence on his followers. Javanese philosophy states that not everyone can become king, only the elected person can be king. Nevertheless, it can still be fought by Laku Brata. Equally with the teacher, not everyone can immediately become a teacher. There are conditions for being a teacher. In Serat Wirid Hidayat Jati mentioned that there are eight things that make people deserve to be a teacher.